Research on the Status of Two-dimensional Layout Circular Parts. Issue 1 (1st February 2022) - Ji, Jun; Xing, Fei-Fei; Zhang, Sai-Kun
Abstract: This paper introduces the research background of the two-dimensional circular part layout problem, analyzes the complexity of the layout problem, studies the current research status of the circular part layout problem, and finally, lists the relationship between layout methods and layout schemes of the two-dimensional circular part layout problem.